Microstructure evolution of CdZnTe crystals irradiated by heavy ions - Lu Liang; Lingyan Xu; Chi Qin; Yingming Wang; Zhentao Qin; Chongqi Liu; Lixiang Lian; Ce Zheng; Yadong Xu; Wanqi Jie (Journal of Materials Research and Technology)
Consideration of irradiation effects is important for in-orbit operation and radiation protection in aerospace applications. The configuration of irradiation defects and their impact on deteriorating the carrier transport properties of CZT crystals need to be clarified. In this study, the microdefect evolution mechanism of CdZnTe (CZT) crystals under 10 MeV Chlorine (Cl) ion irradiation at flux of 1 × 1010∼1 × 1012 n·cm−2 are investigated. The stacking faults first appear in the CZT crystal at 4.5 × 10−4 displacement per atom (dpa), which are categorized into slip-type, gap-type and vacancy-type. In order to hinder the further expansion of stacking fault, S-shaped stacking fault dipole appears. When the dpa reaches 4.5 × 10−2, the local phase transition occurs in the damage zone to form CuPt-A ordered phase with ZnTe/CdTe periodic arrangement because the fluctuation in local composition and strain caused by cascade collisions. The deterioration of electric field distribution and charge collection caused by irradiation damage layer leads to the decrease of γ-ray detection ability. The energy resolution (ER) of the CZT detector for γ-ray can be maintained at 30.6% when the ion flux accumulates to 1 × 1012 n·cm−2, revealing high irradiation hardness. Consequently, these findings provide a theoretical basis for the radiation damage recovery of CZT detectors, further demonstrating that CZT crystals are the most competitive new generation of room-temperature nuclear radiation detection materials, and can provide radiation protection strategies for similar compound semiconductor materials.